MINERALOGICAL FEATURES AND PHYSICOCHEMICAL FORMATION CONDITIONS OF VEIN MINERALIZATION OF THE SOUTHERN FLANK OF THE SAF´YANOVKA MASSIVE SULFIDE DEPOSIT (CENTRAL URALS) - N.P. Safina; A.V. Korovko; I.A. Blinov; N.N. Ankusheva; M.A. Rassomakhin; K.A. Filippova (Минералогия)
The paper presents the results of studies of sulfide and fluorite veins of the southern flank of the Saf´yanovka massive sulfide deposit, Central Urals. The sulfide veins include sphalerite-galena and sphaleritepyrite-chalcopyrite types, in which sulfides are associated with gypsum, carbonates, barite or quartz. Fluorite in host rocks is closely related to carbonates (dolomite, calcite, and siderite), kaolinite and magnesiocarpholite. The sulfide veins differ in chemical composition and rare minerals. In galena-sphalerite veins, the higher Zn, Pb, Cd and Ag content is associated with the presence of sphalerite, galena and tennantite-(Zn) with Ag (up to 1.09 wt %). In sphalerite-pyrite-chalcopyrite veins, the accumulation of Cu, Sn, In, Se, Te and Bi is explained by the presence of tennantite-(Zn), enargite, stannoidite, sakuraiite (?), wittichenite, hessite and Se-bearing galena. The elevated (ppm) Th (1.69) и U (4.79) and REE + Y (447) content is determined in fluorite veins. The REE minerals include fluorcarbonates (synchisite-(Nd) (predominant), synchisite-(Y), synchisite-(Ce) and bastnäsite), which are closely associated with overprinted dolomite and kaolinite. The fluid inclusions study of gypsum from pyrite-chalcopyrite veins showed that the associated Cu mineralization formed from H2O-Na-K chloride fluid at temperatures of 210–150 °С. The fluid, which was responsible for the formation of fluorite veins, contained Na, K, Ca и Mg. The formation temperatures of fluorite range from 190 to 280 °С. New data revealed the peculiarities of mineral composition of rich Cu ores with fluorite and also explain the higher content of some elements, including REEs.